CHINESE DIASPORA IN RUSSIA - A. G. Larin (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2017)
At the present stage, the thesis of the “Chinese demographic threat” has decreased to the lowest level, but has not disappeared completely from the mass consciousness, paradoxically combining with increased sympathy for China. The work of Chinese migrants, spreading throughout the country, plays a particularly significant role in the economy of the Russian Far East. In a number of places and a number of industries, Chinese migrants compete with Russians and even drive them out of the market; In other cases, their work is recognized as necessary. The Russian authorities pursue a policy of gradual restriction of foreign, including Chinese, labor, both to facilitate the employment of their own citizens, and to achieve geopolitical goals. The reverse side of this policy is the worsening of the already not very favorable investment climate in the country. The Russian administration has little control over the economic activities of Chinese migrants and even the dynamics of their numbers, but at the same time it tends to lease to the Chinese side large agricultural and forest territories, not seeking to maximize the labor potential of its people and creating a situation impending damage to the country’s economic sovereignty, that causes public outcry. Educational migration from China to Russia, which is not very large, is constrained by a set of causes, including unfavorable living conditions in Russia. The main reason is the low rating of the Russian diploma in the international labor market, including in China itself, and the very modest opportunities that it opens for career growth. The conjugation of the Eurasian Economic Union and the Silk Road Economic Belt, apparently, will open up wider opportunities for attracting Chinese labor migrants to the rise of the Russian economy, but their professional structure will hardly change qualitatively. The explosive growth of their number can occur if the EAEU and China decide to establish a free trade zone. However, this is unlikely in the foreseeable future. The Chinese diaspora, being undoubtedly useful for Russia, simultaneously carries a number of risks to it. They can be eliminated or mitigated by establishing clear control and regulation of migrants’ activities, but for this it is necessary to improve the mechanism of managing the economy of the country.